Technological innovation and employee psychological well-being: The moderating role of employee learning orientation and perceived organizational support - Zahoor, Nadia; Donbesuur, Francis; Christofi, Michael; Miri, Domnan (My University, 2022)
A significant yet rarely explored research area is how the adoption of technological innovations impacts employee psychological well-being, such as in regard to employee anxiety and satisfaction. Accordingly, this study proposes and tests a framework of the effect of technological innovation on the psychological well-being of employees and how much effect is shaped by employee learning orientation and perceived organizational support. Empirical findings from 202 employees within 40 manufacturing SMEs show an inverted U-shaped relationship between technological innovation and employee psychological well-being (measured as employee anxiety and satisfaction). Further analysis reveals that both employee learning orientation and perceived organization support enhance the inverted U-shaped effect of technological innovation on employee psychological well-being. Our findings present important research and practical implications for innovation and organizational studies literature.
Keywords: Employee learning orientation; Pakistan; Perceived organizational support; Psychological well-being; SMEs; Technological innovation